Projected land‐cover change effects on East African rainfall under climate change - Moore, Nathan; Andresen, Jeffrey A.; Lofgren, Brent M.; Pijanowski, Bryan C.; Kim, Dong Yun (International Journal of Climatology, 2014)
ABSTRACT Both land‐cover/land‐use change ( LCLUC ) and greenhouse gas ( GHG ) concentrations have been shown to influence regional climate, albeit at different spatial scales. In East Africa, climate changes due to changing GHG concentrations are broadly projected to be warmer and wetter. LCLUC projections include trends towards both agricultural intensification and agricultural expansion into savannas, which may result in complex climate interactions and impacts. The primary objective of this study was to examine the regional responses to future GHG , LCLUC , and their combined effects in East Africa, and to better understand how hydrometeorological mechanisms might be altered by LCLUC in future scenarios. In this study, we present high‐resolution decadal simulations from a regional climate model that compare the relative and combined effects of projected LCLUC and GHG . This research suggests that taken separately, these two climate forcings may significantly alter regional precipitation patterns both temporally and spatially but in potentially different and independent ways. In combination, some portions of the region exhibit responses dominated by either LCLUC or GHG effects, but certain areas show complex effects resulting from the combined influence of these two forcings. Perhaps most importantly, the results suggest that projected precipitation changes around major population areas may be as strongly influenced by LCLUC as by GHG effects.
openalex: W1924681293 mag: 1924681293
Keywords: openalex:import